The Effect of Brand Image, Service Quality, and Customer Value on Customer Satisfaction - Rusmahafi, Fikri Aulawi; Wulandari, Ririn (International Review of Management and Marketing, 2020)
This study aims to analyze the effect of Brand Image, Service Quality, and Customer Value on Customer Satisfaction of Bank Muamalat Indonesia. Where, customer satisfaction is part of the formation and to grow market share, in general, and increase the rank of Bank Muamalat in the Islamic Banking Industry. Multiple linear regression analysis was used to test three independent variables namely brand image, service quality, and customer value on customer satisfaction. The research data came from 150 customer respondents who saved at Bank Muamalat Indonesia Ciputat, BSD, and Cipulir branches. The results showed that the brand image variable did not significantly influence the customer satisfaction of Bank Muamalat Indonesia, while the variable service quality and customer value had a significant positive effect on customer satisfaction of Bank Muamalat Indonesia. However, a good reputation, Identical to Islamic Banks, trusted and Islamic, needs to be attached and socialized to strengthen the brand image. On the other hand, the speed of service is a factor of customer satisfaction that needs major attention, and speed of service creates a strong customer value regarding expected performance. Keyword: Islamic Bank, Customer value, Brand Image, Service Quality, Customer Satisfaction JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.9939